The Sources and Educational Consequences of Anthropological Reductionism - Witold Starnawski (Nicolaus Copernicus University in Toruń, 2012)
Reductionist tendencies mean the exclusion of important elements from the conception of man. Theoretical (philosophical) mistakes lead to serious consequences in pedagogy and have destructive influence on educational practices. The author indicates various examples of reductionist thesis, such as: 1) post-Carthesian absolutization of intellect, 2) phenomenalism in the idea of experience, 3) instrumentalism in the definition of truth, 4) linguistic games and stories as the substitution of reality. Anti-reductional attitude is based on acceptance of the fact that reality is the ultimate criterion of knowledge and search for the truth wherever it is. The cultivation of ability of transcendence, an agreement for un-instrumental character of a person (and education), proper understanding of a duty and spirituality are adequate responses to reductionist tendencies.